The night before Christmas - Moore, Clement Clarke, 1779-1863; Harness, Cheryl (New York : Random House, 1989)
Saint Nicholas visits a sleeping household on Christmas Eve.
Keywords: Santa Claus -- Juvenile poetry; Christmas poetry; Children's poetry, American; Santa Claus -- Poetry; Christmas -- Poetry; Narrative poetry; American poetry